2018
DOI: 10.1172/jci.insight.99445
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil accumulation and NET release contribute to thrombosis in HIT

Abstract: Heparin-induced thrombocytopenia (HIT) is an immune-mediated thrombocytopenic disorder associated with a severe prothrombotic state. We investigated whether neutrophils and neutrophil extracellular traps (NETs) contribute to the development of thrombosis in HIT. Using an endothelialized microfluidic system and a murine passive immunization model, we show that HIT induction leads to increased neutrophil adherence to venous endothelium. In HIT mice, endothelial adherence is enhanced immediately downstream of nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 129 publications
(183 citation statements)
references
References 60 publications
(78 reference statements)
5
178
0
Order By: Relevance
“…PF4 binds to and aggregates polyanions like heparin 26 . We and others have found that PF4 similarly aggregates NETs, physically compacting them, and enhancing their resistance to endogenous and microbial nucleases 27,28 . We speculated that this activity may be, in part, responsible for our previous observation that PF4 enhances survival in murine lipopolysaccharide (LPS) endotoxemia 29 .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…PF4 binds to and aggregates polyanions like heparin 26 . We and others have found that PF4 similarly aggregates NETs, physically compacting them, and enhancing their resistance to endogenous and microbial nucleases 27,28 . We speculated that this activity may be, in part, responsible for our previous observation that PF4 enhances survival in murine lipopolysaccharide (LPS) endotoxemia 29 .…”
Section: Introductionmentioning
confidence: 74%
“…The infusion of wild-type (WT) mice with platelets obtained from hPF4 + animals improved survival 29 . We have recently found that PF4 binds to NETs, leading them to become physically compact and DNase resistant 27 .…”
Section: The Effect Of Pf4 On Plasma Levels Of Ndps In Murine Endotoxmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated endothelium also releases von Willebrand factor, which binds PF4 and HIT antibodies, promotes platelet adhesion and additional PF4 release, creating a feed-forward prothrombotic pathway. 140 HIT immune complexes assembling on PF4 bound to GAGs expressed on monocytes signal through Fcγ receptors to stimulate production of thrombin that transactivates platelets in concert with their direct activation by HIT antibodies. Neutrophils activated by HIT antibodies adhere to venous endothelium, accumulate downstream of the evolving thrombus, and contribute to venous thrombosis at least partially through a peptidyl arginine deiminase 4 (PAD4)-dependent pathway.…”
Section: Neutrophilmentioning
confidence: 99%